2010
DOI: 10.1016/j.jvb.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Role resources and work–family enrichment: The role of work engagement

Abstract: The majority of work-family research has focused on negative spillover between demands and outcomes and between the work and family domains (e.g., work-family conflict; see review by Eby, Casper, Lockwood, Bordeaux, & Brinley, 2005). The theory that guided this research was in most cases role stress theory (Greenhaus & Beutell, 1985) or the role scarcity hypothesis (Edwards & Rothbard, 2000). However, according to spillover theory, work-related activities and satisfaction also affect non-work performance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
235
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(265 citation statements)
references
References 46 publications
(62 reference statements)
18
235
0
12
Order By: Relevance
“…Resource variables differentially mediated the relationship between TL and WFC and WFE, underscoring the related, yet distinct, nature of these constructs (Carlson et al, 2006). The present study further adds to empirical tests of Greenhaus and Powell's model of WFE (Siu et al, 2010). Managerial support for workfamily was a significant mediator for both WFE and WFC, and showed the strongest effects of all mediators.…”
Section: Summary and Implications For Theorysupporting
confidence: 58%
“…Resource variables differentially mediated the relationship between TL and WFC and WFE, underscoring the related, yet distinct, nature of these constructs (Carlson et al, 2006). The present study further adds to empirical tests of Greenhaus and Powell's model of WFE (Siu et al, 2010). Managerial support for workfamily was a significant mediator for both WFE and WFC, and showed the strongest effects of all mediators.…”
Section: Summary and Implications For Theorysupporting
confidence: 58%
“…For example, a study on work-family conflict among Malaysian employees has shown that informal workplace family support (such as greater discretion in managing work, and granting approval to leave work earlier than usual to deal with urgent family matters) has the potential of reducing work-family conflict (Aminah & Zoharah, 2013). Work-family facilitation can be enhanced by providing autonomy to employees (Baral & Bhargava, 2008;Innstrand et al, 2010;Siu et al, 2010) since autonomy is laden with resources including time-management skills, initiative, and self-confidence (Voydanoff, 2004) which could be applied to family activities. Another initiative is to increase employee job involvement since this is linked to work-family facilitation (Aryee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[3], core self-evaluations [4] and work engagement [5]. At Family level, FWE arises from the support received in family domain [3,4].…”
Section: Antecedentsmentioning
confidence: 99%